2016 IEEE 23rd International Conference on Software Analysis, Evolution, and Reengineering (SANER) 2016
DOI: 10.1109/saner.2016.116
|View full text |Cite
|
Sign up to set email alerts
|

Release Practices for Mobile Apps -- What do Users and Developers Think?

Abstract: Large software organizations such as Facebook or Netflix, who otherwise make daily or even hourly releases of their web applications using continuous delivery, have had to invest heavily into a customized release strategy for their mobile apps, because the vetting process of app stores introduces lag and uncertainty into the release process. Amidst these large, resourceful organizations, it is unknown how the average mobile app developer organizes her app's releases, even though an incorrect strategy might bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 31 publications
1
42
0
1
Order By: Relevance
“…They found evidence that more mentions of features and fewer mentions of bug fixing can increase the chance for a release to be impactful rating, then they explored findings from app store comprehensively in 1 study and pointed out which have a direct and actionable impact on software teams, release planning, techniques for requirements engineering, software design, security, and testing. Also, studies tried to explore reasonable release strategies for mobile apps in their evolution process. Nayebi et al performed 2 surveys with users and developers; they found that the release date and frequency is not a decisive factor to install an app, and users prefer to install apps that are updated more recently and less frequently.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…They found evidence that more mentions of features and fewer mentions of bug fixing can increase the chance for a release to be impactful rating, then they explored findings from app store comprehensively in 1 study and pointed out which have a direct and actionable impact on software teams, release planning, techniques for requirements engineering, software design, security, and testing. Also, studies tried to explore reasonable release strategies for mobile apps in their evolution process. Nayebi et al performed 2 surveys with users and developers; they found that the release date and frequency is not a decisive factor to install an app, and users prefer to install apps that are updated more recently and less frequently.…”
Section: Related Workmentioning
confidence: 99%
“…Also, studies tried to explore reasonable release strategies for mobile apps in their evolution process. Nayebi et al performed 2 surveys with users and developers; they found that the release date and frequency is not a decisive factor to install an app, and users prefer to install apps that are updated more recently and less frequently. Villarroel et al presented a tool supporting the release planning activity of mobile apps by mining information from user reviews.…”
Section: Related Workmentioning
confidence: 99%
“…A 2015 survey [34] shows that 77% of the users will not download an app that has a star rating which is lower than 3 stars. In addition, Nayebi et al [29] find that app developers often deviate from their time-based release scheduling in order to address issues that are raised in user reviews. Consequently, it is important for apps to achieve high star ratings and good user reviews.…”
Section: Studying the Consistency Of Star Ratings And The Complaints mentioning
confidence: 99%
“…Heterogeneity of mobile databases, complexity in mobile applications development [1] as well as the mobile devices themselves has engineered several obstructions in data synchronization. Data Synchronization (DS) can be defined as record exchange between two different databases [2].…”
Section: Introductionmentioning
confidence: 99%